Students' Perception of Co-teaching In an Inclusive Classroom: Implementation of The Finnish Education Curriculum - Salma Yuliani; Rasmitadila Rasmitadila; Shakilla Azzahra; Siti Fadhila Nursyahida; Naya Sabrina (Research Synergy Foundation, 2025)
Implementing instruction in inclusive classes in elementary schools requires a flexible and effective co-teaching model that can be carried out collaboratively between teachers so that the learning objectives of all students can be achieved. However, various problems with co-teaching practices in inclusive classes, such as differences in responsibilities and roles between teachers, lack of collaboration, and lack of communication between teachers, often occur, including in Indonesia. This study explores prospective teacher students' perceptions regarding implementing co-teaching in inclusive classes in the context of the Finnish education curriculum. Data were collected through semi-structured interviews with six students who had implemented co-teaching practices. Data were analyzed using thematic analysis. The study produced three main themes: supporting factors for implementing co-teaching, challenges in using co-teaching, and teacher professionalism. The findings show that a flexible and effective co-teaching model in inclusive classes can only be practiced if all teachers strongly commit to collaborating as equal partners, increasing qualified teacher professional development, and school support to serve all students in achieving their most significant potential. This research has implications for all stakeholders in supporting and providing all the determining factors for co-teaching success, including the competence of quality teachers and prospective teacher students in higher education to meet the learning objectives for all students in inclusive classes.